Cloning Gene Encoding Micronema 3 (Mic3) Protein of Tachyzoite Toxoplasma Gondii Local Isolate - Wayan T. Artama; Ni Nyoman Ayu Dewi; Didik Tulus Subekti (Universitas Gadjah Mada, 2005)
Microneme 3 (MIC3) protein tachyzoites Toxoplasma gondii is one of protein which plays an important role during cell host invasion. Gene encoding MIC3 protein has been studied and it was suggested a potent vaccine candidate against Toxoplasma gondii infection. The aim of this research is to clone and sequence the gene encoding MIC3 protein of tachyzoites Toxoplasma gondii local isolate by amplification using polymerase chain reaction with specific primers. The amplified DNA fragment was cloned into pGEM-T and transformed into E. coli XL-1 Blue by heat shock method. Recombinant plasmids were isolated using alkali lysis method and analyzed by digestion using restriction endonuclease enzymes PstI, HindIII, NcoI and EcoRV. The recombinant plasmids then sequenced to find out the nucleotide sequence of insert gene by ABIPRISM 377 DNA Sequencer. The DNA sequence then were analyzed by computer software for alignment. The result showed that transformation in E. coli XL-1 Blue by pGEM-T produced one clone that was encoding MIC3 protein. Analysis of 489 bp from 5’ and 447 from 3’ of gene sequence showed 97-98% homology with gene encoding for MIC3 protein of RH isolate.